Knowledge that Acts: Evaluating the Outcomes of a Knowledge Brokering Intervention in Western Australia’s Ningaloo Region - Chapman, K.; Boschetti, F.; Fulton, E.; Horwitz, P.; Jones, Tod; Scherrer, P.; Syme, G. (2017)
Knowledge exchange involves a suite of strategies used to bridge the divides between research, policy and practice. The literature is increasingly focused on the notion that knowledge generated by research is more useful when there is significant interaction and knowledge sharing between researchers and research recipients (i.e., stakeholders). This is exemplified by increasing calls for the use of knowledge brokers to facilitate interaction and flow of information between scientists and stakeholder groups, and the integration of scientific and local knowledge. However, most of the environmental management literature focuses on explicit forms of knowledge, leaving unmeasured the tacit relational and reflective forms of knowledge that lead people to change their behaviour. In addition, despite the high transaction costs of knowledge brokering and related stakeholder engagement, there is little research on its effectiveness. We apply Park’s Manag Learn 30(2), 141–157 (1999); Knowledge and Participatory Research, London: SAGE Publications (2006) tri-partite knowledge typology as a basis for evaluating the effectiveness of knowledge brokering in the context of a large multi-agency research programme in Australia’s Ningaloo coastal region, and for testing the assumption that higher levels of interaction between scientists and stakeholders lead to improved knowledge exchange. While the knowledge brokering intervention substantively increased relational networks between scientists and stakeholders, it did not generate anticipated increases in stakeholder knowledge or research application, indicating that more prolonged stakeholder engagement was required, and/or that there was a flaw in the assumptions underpinning our conceptual framework.